1999
DOI: 10.1046/j.1525-1497.1999.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Treating depression in staff-model versus network-model managed care organizations

Abstract: Whereas the providers from staff/group-model MCOs had greater access to and relied more on referral, the providers from network-model organizations were more likely to treat depression themselves. Given varying attitudes and behaviors, improving primary care for the treatment of depression will require unique strategies beyond enhancing technical knowledge for the two types of MCOs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 32 publications
3
74
0
Order By: Relevance
“…Moreover, the juxtaposition of differences from guidelines with the various reported barriers to appropriate care for each clinic (Table 3) suggests that that individual practices will have specific needs for targeting quality improvement activities and tailoring interventions to local context. While this study is most applicable to VA and other staff-model managed care settings (Meredith, et al 1999), our findings have similar implications to those from non-VA settings. For example, we found that antidepressants were the main or only treatment modality reported by the clinical leaders.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Moreover, the juxtaposition of differences from guidelines with the various reported barriers to appropriate care for each clinic (Table 3) suggests that that individual practices will have specific needs for targeting quality improvement activities and tailoring interventions to local context. While this study is most applicable to VA and other staff-model managed care settings (Meredith, et al 1999), our findings have similar implications to those from non-VA settings. For example, we found that antidepressants were the main or only treatment modality reported by the clinical leaders.…”
Section: Discussionsupporting
confidence: 62%
“…We show, however, that the basic characteristics of these clinics are similar to national VA averages. VA PC clinician attitudes and practices have also been shown to be similar to those of clinicians in non-VA staff/group model organizations (Meredith et al 1999). Our basic findings regarding the need to consider variations in usual care should extrapolate to other settings.…”
Section: Discussionmentioning
confidence: 62%
“…While this information has yielded useful insights into implementation issues (Rubenstein et al 1999;Meredith et al 1999Meredith et al , 2001, the measures incorporated were typically based more on practical experience than conceptual understanding, and have proved difficult to use in unpacking the implementation and dissemination process, linking those to intervention outcomes, and generalizing findings across studies.…”
Section: Studying Interventions In Context: Research Questions and Apmentioning
confidence: 99%
“…For example, in our Partners in Care study of QI for depression, differences in turnover and the personalities and skills of key personnel across the 46 participating primary care sites were considered likely factors affecting the enthusiasm for the study and behavior of intervention providers, such as the persistence and creativity displayed by nurse case managers in following up with elusive patients (Rubenstein et al 1999). In the Witness for Wellness initiative, the goals of both academic and community partners have shifted-the former evolving from disseminating the specific Partners in Care findings to an emphasis on enabling communityderived strategies to improve depression care, and the latter focusing on methods more consistent with evaluation and partnership strategies more explicitly documented ).…”
Section: Stages Of Diffusion-muchmentioning
confidence: 99%
“…Although referrals from primary care to specialty mental healh care have increased, they remain low, at about five referrals per family practitioner per year [19, 20]. PCCs reporting poor access to mental health specialists as a barrier tend not to refer, instead providing depression treatment themselves [21]. …”
Section: Discussionmentioning
confidence: 99%